[sumlimits_{x=1}^{n-2} sumlimits_{y=1}^{m-2} sumlimits_{i=1}^{n-x-1} sumlimits_{j=1}^{m-y-1} i(n-i-x)j(m-j-y)
]
[sumlimits_{x=1}^{n-2} sumlimits_{i=1}^{n-x-1}i(n-i-x) sumlimits_{y=1}^{m-2}sumlimits_{j=1}^{m-y-1} j(m-j-y)
]
[F(n-2)*F(m-2)
]
[egin{aligned}
F(n-2)&=sumlimits_{x=1}^{n-2} sumlimits_{i=1}^{n-x-1}i(n-i-x) \
&=sumlimits_{x=1}^{n-2} sumlimits_{i=1}^{n-x-1}(n-x)i-i^2 \
&=sumlimits_{x=1}^{n-2} [(n-x)sumlimits_{i=1}^{n-x-1}i-sumlimits_{i=1}^{n-x-1}i^2 ]\
&=sumlimits_{x=1}^{n-2} frac12(n-x)^2(n-x-1)-frac16(n-x-1)(n-x)(2n-2x-1)\
&=frac16 sumlimits_{x=1}^{n-2} (n-x-1)^3+3(n-x-1)^2+2(n-x-1)\
&=frac16S_3(n-2)+frac12S_2(n-2)+frac13S_1(n-2)
end{aligned}
]